1999
DOI: 10.1007/s004180050402
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of staurosporine-induced apoptosis by comet and annexin V assays

Abstract: Comet, TUNEL, and annexin V assays were used to identify DNA fragmentation and plasma membrane alterations occurring during staurosporine-induced apoptosis in Chinese hamster ovary cells. TUNEL assay detected apoptotic cells after 6 h treatment. The occurrence of annexin V immunofluorescence staining after 1 h treatment confirms that exposure of phosphatidylserine (PS) residues is an early biochemical feature of apoptosis. According to intensity, three annexin staining patterns were distinguished, related to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
46
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 30 publications
10
46
0
Order By: Relevance
“…The alkaline single cell gel electrophoresis assay (Comet assay) was developed to assess DNA fragmentation typical of toxic DNA damage and of early-stage apoptosis (14,15). This assay, when electrophoresis is performed at pH Ն13, provides a sensitive means of analyzing alkali-labile sites and singleand double-strand DNA breaks in small number of cells.…”
Section: Chemicals N-acetylcysteine (Nac) Was Obtained Frommentioning
confidence: 99%
“…The alkaline single cell gel electrophoresis assay (Comet assay) was developed to assess DNA fragmentation typical of toxic DNA damage and of early-stage apoptosis (14,15). This assay, when electrophoresis is performed at pH Ն13, provides a sensitive means of analyzing alkali-labile sites and singleand double-strand DNA breaks in small number of cells.…”
Section: Chemicals N-acetylcysteine (Nac) Was Obtained Frommentioning
confidence: 99%
“…34,35 The terminal deoxynucleotidyl transferasemediated dUTP nick-end labeling (TUNEL) assay has also proved to be a sensitive and reliable method for measuring DNA strand breaks. However, the detection of highly damaged cells by the Comet assay occurred earlier than the detection of DNA modifications by the TUNEL assay 36 and more sensitively. 37 SCGE allowed a rapid analysis of genotoxic damage in individual nuclei such as flow cytometry, and a significant strong correlation was shown 38,39 with a higher sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Comets from the apoptotic bodies are generally Unwinding in 30 mM NaOH, 2 mM EDTA for 20 min at RT; electrophoresis in 30 mM NaOH for 4 min at 0. shorter than 20 m, although such comets were rarely observed in this study. The lysis and electrophoresis conditions used in the present study were different from those used in most of the comet assay methods reported for detecting DNA fragmentation (7,11,13,15,17,18). Whereas the present method mainly used anionic detergents and a neutral lysis condition (pH 9.5) followed by electrophoresis at nearly neutral or low alkaline pH (8.3), previous studies have generally used high-salt lysis at low alkaline pH followed by neutral or alkaline electrophoresis.…”
Section: Discussionmentioning
confidence: 92%
“…Alkaline and neutral versions of the assay have been developed that predominantly detect singleand double-strand breaks, respectively (5,6). Due to its ability to detect DNA breaks, comet assay also has been used in the detection of DNA fragmentation during apoptosis (7)(8)(9)(10)(11)(12). The neutral version of the assay is preferred for this purpose due to its specificity for double-strand breaks (13).…”
Section: Discussionmentioning
confidence: 99%